CRANIAL MORPHOMETRICS OF THE APENNINE BROWN BEAR (URSUS ARCTOS MARSICANUS) AND PRELIMINARY NOTES ON THE RELATIONSHIPS WITH OTHER SOUTHERN EUROPEAN POPULATIONS - LOY, Anna; GALFO M; GENOV P; VIGNA TAGLIANTI A. (Italian Journal of Zoology, 2008)
The geographic variation of seven southern European populations of Ursus arctos was investigated through multivariate morphometrics of the skull. Univariate and multivariate analyses were run on 63 cranial and dental measurements recorded on 50 specimens from the Apennines, the Alps, and the Transcaucasus, and on 14 specimens of the fossil Ursus spelaeus. Detailed analyses of sexual dimorphism, age structure, and ranges of variation have been carried out on the Apennines population, which morphological variation has been little explored. Subsets of characters were selected to allow comparison with data derived from literature for populations from the Pyrenees, the Rhodopi-Rila-Pirin, the Balkans, and the Caucasus. Analyses clearly indicate that the Apennine bear is morphologically distinct from both a western (Alps, Pyrenees, Balkans, and Rhodopi) and an eastern contingent (Caucasus and Transcaucasus), therefore suggesting that the Apennine population should be reconsidered as a separate taxon, namely Ursus arctos marsicanus. These preliminary results suggest caution in restocking conservation actions.